POLISH TEXTBOOK MARKET (1970–2012): CHANGES AND TENDENCIES - JABŁOŃSKA-STEFANOWICZ, EWA (Knygotyra, 2014)
This paper analyzes the Polish market of textbooks in the last four decades with reference to the political, social, and technological changes of that period. The whole span of forty years can be divided into two stages – before and after 1989. The analysis concerns the three key actors involved in communication through books: the author, publisher, and the recipient. It was investigated how the social status and independence of these actors have changed over time. The description is not of a quantitative character and it only allows to identify the tendencies in the analyzed field. After the period of the publisher’s monopoly, when any publishing house was an emanation of the power of political authorities, there came the time of the recipient’s (teacher’s) importance. With the introduction of free market principles the teacher became the actor who selects textbooks out of many and thus influences not only the profit but also the future of the publisher. Free electronic resources, announced in the program „Cyfrowa Szkola” (2012), lead to an increasing independence of the teacher. A part of his new tasks used to belong to the publisher.